Sudden death - Menzies, Robert; Carlyon, Terry (Australasian video online, 2003)
The mystery of a deadly inheritance that strikes at random and is lethal within minutes. Sudden unexplained death is the cruelest of killers, striking at random and leaving loved ones distraught and without answers. Professor Michael Denborough has devoted his life to finding the cause of some of these deaths. Sudden Death tracks this unconventional scientist's research into a rare genetic disorder that may help unlock the riddle of Sudden Infant Death Syndrome (SIDS), and other unexplained deaths. This is the amazing story of Malignant Hyperthermia and the enigmatic and award-winning medical scientist who has dedicated his life to solving its mystery.